Calculation method for the amount of contaminant oil during sequential transportation through product oil pipelines. Issue 4 (July 2020) - Liu, Enbin; Li, Wensheng; Cai, Hongjun; Qiao, Weibiao; Azimi, Mohammadamin
A considerable amount of oil contamination is caused by the presence of the trailing oil. This paper aims to simulate and analyze the influences of trailing oil on the quality of oil products in undulating sections. By studying the formation mechanism of mixed oil at inclining pipeline sections and the influences of velocity and oil batches on incline sections, as well as both ups and downs, the correlation is obtained between replacement time of different batches and velocity at various sections. By applying FLUENT 14.5, the maximum time of volume fraction of contaminant oil from 1% to 99% is simulated at cross-sections among different pipeline sections. Aiming at the relationship between oil product replacement time and change time of mixing section volume fraction and flow velocity, the mixing increment of undulating section relative to straight section is obtained. Combining with the empirical mixing length calculation equation, the equation for calculating mixing length considering terrain undulation is obtained. Combined with the actual operation data of Lan-Chengyu's product oil pipeline, the error of the new mixed oil length calculation equation and actual oil mixing is 0.7966%. Excessive cutting amount of mixed oil will result in the waste of refined oil, and the less cutting amount will cause pollution of refined oil. The new mixed oil length calculation equation can more accurately guide the oil mixing cutting work at the oil station.